Kualitas fisik dan fraksi serat silase rumput Gajah (Pennisetum purpureum) dengan penambahan molasses dan probiotik - Lilis Riyanti; Gian Febriza (Politeknik Negeri Jember, 2023)
The objective of the study was to analyze the use of molasses as an energy source of silage and probiotics on the physical/organoleptic quality of silage, fermentation characteristics, and NDF and ADF silage content. 15 kgs of Napier grass were packed in plastic silos for each treatment and stored for 21 days. The experiment used a completely randomized design (CRD) with 3 treatments and 4 replications. The treatment consisted of P0: control or the Napier grass silage, P1: Napier grass silage + 3% molasses, and P2: Napier grass silage + 3% molasses and EM4 probiotics. The data were tested by using an analysis of variance and the differences among treatment means were examined by the Least Significant Difference (LSD) test. The variables measured were organoleptic quality including color, odor, texture, presence of fungi, fermentation characteristics including pH, dry matter (DM), and fleigh value as well as the content of Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF). The results showed that the molasses and probiotics addition had no significant effect on the color, odor, and texture of the silage (P>0.05) but had a significant effect on the presence of fungi (P<0.01). Molasses and probiotics addition as fermentation additives reduced the pH value and increased the value of fleigh silage (P<0.05) but did not affect the increase of silage dry matter (P>0.05), decreased the NDF content (P<0.05) and had no significant effect on the ADF content. The conclusion of the research was the addition of molasses as an energy source, as well as a combination of molasses and EM4 probiotics can improve the fermentative quality of silage, by decreasing the pH value, increasing the fleigh value, and being able to reduce the NDF content of silage.